The legends of the saints in Old Norse-Icelandic prose - Wolf, Kirsten, 1959- (Toronto [Ontario] : University of Toronto, 2013)
With The Legends of the Saints in Old Norse--Icelandic Prose, Kirsten Wolf has undertaken a complete revision of the fifty-year-old handlist The Lives of the Saints in Old Norse Prose.
I. Catalogues and Bibliographies -- II. Collections and Anthologies -- III. General Works -- IV. Essay Collections, Festschrifts, and Conference Proceedings -- V. Individual Legends.
Includes bibliographical references.
Keywords: Old Norse prose literature -- Bibliography; Christian saints -- Legends -- Early works to 1800 -- Bibliography; Christian saints in literature -- Bibliography; REFERENCE / Bibliographies & Indexes; Electronic books; Electronic books